Análise comparativa da avaliação funcional dos pavimentos da Universidade Federal Rural do Semi-Árido – Campus Mossoró - Silva, Caroliny Martins (Universidade Federal Rural do Semi-Árido, 2019)
One of the main objectives of the transport infrastructure is to ensure continuous trafficability in diverse climatic conditions, providing users with rolling comfort and safety. The need for timely and adequate maintenance of the road network, due to the aging of the pavements, was one of the reasons that led to the increasing development and application of Pavement Management Systems (GSP). The GSP is used as a tool to improve pavement maintenance proposals by optimizing the use of available resources. In this way, the present work has as objective the accomplishment of two of the basic activities of a GSP: to create a database and to carry out the evaluation of the pavements of the campus of UFERSA Mossoró. For this, using free tools like Google My Maps and QGIS, it was possible to perform the cataloging and characterization of the routes; with the georeferenced data system, the UFERSA inventory was obtained. From a total of 9.6 km of existing roads, approximately 4.5 km are made up of roads with asphalt pavement. In a sample, 12% of the total extent of the asphalt was evaluated. Following the recommendations of the National Department of Transport Infrastructure, DNIT 006/2003-PRO and DNIT 008/2003-PRO, the Global Severity (IGG) Index and Continuous Visual Survey (LVC) methods were used, respectively, as evaluation procedures. At the end of the work, a comparative analysis is performed between the methods studied and it is verified that, conceptually, the roads of the university campus are presented as optimal or regular in relation to the existing asphalt pavement. It was also verified that the tools obtained free of charge were shown as effective and economical ways to perform the characterization of the surface condition of the roads.
Monografia
Keywords: Infraestrutura de transportes; Gerência de pavimentos; Avaliação de superfície de pavimentos; Transport infrastructure; Pavement management; Evaluation of pavement surface; ENGENHARIAS::ENGENHARIA CIVIL